Kontrwywiad jako jedna z funkcji wywiadu gospodarczego - Rzewuska, Monika (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The article describes one of the basic functions of the business intelligence - counter-intelligence. The author gives the definition of counter-intelligence and then describes its main tasks and functions. The article discusses the protection of the acquired possessions of the intellectual firm and also methods of the defence against intelligence activities of the competition. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1086, s. 222-228